Acquired brain injury and the unraveling of theory of mind: exploring the role of personality change and spatial cognition - Mosdell, Jill (Department of Psychology, 2025)
This study investigates the intricate relationship between spatial cognition, personality changes (notably egocentrism), and Theory of Mind (ToM) following right hemisphere dysfunction (RHD) due to Acquired Brain Injury (ABI). Given the critical role of the right hemisphere in social and emotional behavior, this research focuses on understanding the connection between ToM and personality alterations, particularly as they relate to Cluster B personality traits postinjury. Through an exploration of right hemisphere syndrome deficits, including anosognosia and spatial neglect, the study aims to provide lesion-based insights into how ToM, spatial cognition, and personality changes interrelate post-ABI. The research is organized into two distinct phases: acute and chronic. It addresses three core objectives: firstly, to clarify the relationship between visuo-spatial abilities and ToM, hypothesizing that RHD adversely affects these capabilities and their interplay. Secondly, to examine the impact of ABI on Cluster B personality changes and their relationship to ToM, with a focus on narcissistic traits such as empathy, self-insight, and social interaction. Thirdly, to analyze ToM task performance in RHD individuals, especially in tasks like the Faux Pas test, controlling for executive functioning and intelligence. Employing both qualitative and quantitative methods, this study provides a unique perspective on RHD patients who maintain core cognitive abilities yet exhibit significant changes in social cognition and personality. Integrating insights from psychoanalysis, developmental, and abnormal psychology, the research enhances the understanding of ToM in the context of cognitive changes post-neurological impairment. This approach offers a comprehensive view of how patients adapt to brain injuries affecting their social and spatial cognitive functions. This study underscores the need for future ToM research to consider the impact of spatial cognition and personality traits. It highlights how these factors compound the loss of cognitive ToM abilities, leading to substantial alterations in patients' relationships and perceptions of the world. The findings emphasize the profound changes in ways of relating to self and others postneurological trauma, reinforcing the importance of a holistic understanding of ToM in clinical neuropsychology.